Basal diet and indigestible marker influence apparent digestibilities of nitrogen and amino acids of cottonseed meal and soybean meal in pigs - Prawirodigdo, Susanto (Anim Nutr, 2019)
This study was to determine the apparent ileal nitrogen (N) and amino acid digestibilities of cottonseed meal (CSM) and soybean meal (SBM) in simple carbohydrate-based and more complex wheat-based diets. Twenty five Large White × Landrace boars (40.9 kg) were randomly allocated to one of 5 dietary treatments: a wheat diet, 40% CSM in either a sugar:starch (1:1) or wheat-based diet, or 40% SBM in either a sugar:starch or wheat-based diet for 14 d. All diets contained vitamins, minerals, and contained acid-insoluble ash (AIA) and Cr(2)O(3) as indigestible markers. Rations were offered (1,800 g/pig per d) in 3 meals/d on d 1 – 11 and 8 meals/d on d 12 – 13. On d 14, the pigs were fed hourly for 8 h. After the 8th meal, pigs were anaesthetised with isoflurothane, and ileal and faecal digesta sampled from the terminal ileum and rectum before lethal injection of barbiturate. Apparent ileal digestibility (AID) of N was greater (12.1%) when CSM was fed in the wheat-based diet as compared to the simple carbohydrate-based diet, whereas apparent ileal N digestibility of SBM was slightly lower (−4.5%) in the wheat-based diet as compared to the sugar:starch-based diet. Apparent ileal amino acid digestibility generally respondeds similarly to N. Therefore, while there was a wide difference in apparent N and amino acid digestibilities of SBM and CSM when they were fed in the sugar:starch-based diets, these differences were less apparent when they were fed the wheat-based diet. There was an apparent net release of N into the hindgut of pigs fed CSM in both base diets. Conversely, there was quite substantial apparent digestion of N in the hindgut of pigs fed SBM in both base diets. The use of Cr(2)O(3) as an indigestible marker resulted in lower apparent ileal and faecal digestibilities than using AIA, particularly for diets containing CSM. These data demonstrate that the basal diet and choice of indigestible marker can substantially influence the estimate of apparent N digestibility, this response can differ for different protein meals.